Nature hide & seek. Rivers & lakes - Wood, John Norris; Dean, Kevin (New York : Knopf : Distributed by Random House, 1993)
Presents information about various freshwater creatures found in lakes and rivers around the world. Gatefold pages challenge the reader to find camouflaged wildlife in underwater scenes.
"Five fold-out panoramas inside"--Cover.
Keywords: Stream animals -- Juvenile literature; Lake animals -- Juvenile literature; Picture puzzles -- Juvenile literature; Toy and movable books -- Specimens; Stream animals; Lake animals; Picture puzzles; Toy and movable books